Understanding WMI scripting - Lissoir, Alain (Amsterdam ; Boston : Digital Press, 2003)
Understanding WMI Scripting explains to Windows and Exchange Administrators how they can use the Windows Management Instrumentation (WMI) scriptable technology available in these products to ease their day-to-day management tasks. Under Windows.NET and Exchange 2000 (SP2), Microsoft is making solid enhancements in WMI. This will dramatically extend the scripting and manageability capabilities of Windows and Exchange. Illustrated with more than three hundred samples, the book links practical problems encountered by administrators to applicable scriptable solutions. Lissoir focuses not on MI programming aspects for developers but on how administrators can use what is available in Windows and Exchange for their admin work. WMI is a very important topic under Windows.NET and Exchange 2000 (SP2), so this book provides real added value to Windows/Exchange administrators. Although Exchange relies on Windows, no other book combines coverage of Windows and Exchange. Fine tune management of Windows servers Achieve better system management and customize critical operations Access hundreds of usable scripts in book and downloadable from web.
Windows script host -- Starting with WMI -- The WMI query language -- Scripting with WMI -- Advanced WMI scripting techniques -- The WMI events scripting.
Keywords: Microsoft Windows (Computer file).; Operating systems (Computers).; Programming languages (Electronic computers).; Electronic books